Primary Science Curriculum Guide. - Stringer, John (Taylor & Francis, 2013)
This guide provides trainee teachers with an insight into the nature and teaching of primary science. It aims to introduce you to the ways in which children learn science, and to the science itself. Each Unit can be studied independently or used to support/prepare for school experiences. You will be directed towards additional reading, which will develop or confirm the subject knowledge you will need to achieve QTS. the curriculum guide is up-to-date, revised to take account of Curriculum 2000 and accepted 'good practice' in primary science teaching and learning. It is also fl.